Suspected cutaneous leishmaniasis in a sample of Westerns Sicily residents: what correlation with occupation? - Verso, Maria Gabriella; Vitale, Fabrizio; Castelli, Germano; Bruno, Federica; Migliazzo, Antonella; Bongiorno, Maria Rita; Santi, Fiorella; Pistone, Giuseppe; Amodio, Emanuele; Picciotto, Diego (La Medicina del Lavoro, 2017)
Background: Leishmaniasis is a widespread infectious disease, but there is not much information about its prevalence in high risk occupational categories. Objectives: The aim of this study is to assess the prevalence of Leishmania immunological positivity in human skin tissues collected from subjects living in Western Sicily, with suspected cutaneous Leishmania infection, in order to explore the risk possibly related to occupation. Methods: 318 consecutive subjects (M/F ratio=1.0, mean age=40±25.4 years), attending the Dermatology Department of the University of Palermo Hospital from 2013 to 2015, without any previous history of Leishmania infection and performing various occupations, were included. Parasite isolation and PCR-RT test on skin scrapings were performed to evaluate the immunological status; all data were analyzed by the chi square test, comparing all positive results from the different provinces. Results: 81 (50.9%) out of 159 females and 79 (49.7%) out of 159 males were found PCR-RT positive to Leishmania infantum, with a higher risk in the Agrigento district (p